American Journal of Dance Therapy Publication of the American Dance Therapy Association - Downey, Laura; Kierr, Susan; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
American Journal of Dance Therapy informs the international mental health community on the latest findings in dance/movement therapy theory, research, and clinical practice by presenting original contributions, case material, reviews, and studies by leading practitioners and educators in the field. The journal, reflecting the dramatic expansion of the profession over the last half-century, publishes timely articles on working with new populations, changing goals, innovative techniques, and new methods of training. Current professional issues, outcome research, and assessment tools are also examined and evaluated. This biannual forum encourages dance/movement therapists and allied mental health professionals to test their theoretical premises and share their ideas. It is a valuable resource for administrators, psychiatrists, psychologists, social workers, and creative arts therapists in the disciplines of music, art, and drama.
Keywords: Education; Clinical psychology; Health psychology; Personality; Social psychology; Clinical Psychology; Health Psychology; Personality and Social Psychology; Education, general